Numerical Experiment for the Determination of the Stress-Strain Condition of the System â€œBasis â€“ Vibroreinforced Soil-Cement Pileâ€ - Anton, Hasenko; Oleksandr, Novytskyi; ., . (International Journal of Engineering and Technology, 2018)
The order of model creation and results of numerical finite element analysis on electronic computers of models of the vibroreinforced soil-cement piles is considered. The pile in the basis (soil) is in volumetric load-bearing conditions, therefore, among the features of creating such a model, the order of application of the load system and the laying of fastenings on its surface is described. Full-scale tests for vertical static load of investigated constructions have been carried out, as a result of which the vibroreinforced soil-cement pile has been destroyed. Surveys and investigations of the type and destruction mechanics were carried out. Revealed places that need to be strengthened. The results of numerical simulation are compared with the results of field tests. The analysis of the mechanics of destruction of the vibroreinforced soil-cement pile is carried out.Â